USE OF PHASE-CONTRAST MAGNETIC RESONANCE IMAGING TO QUANTIFY CEREBROSPINAL FLUID DYNAMICS IN PATIENTS WITH COMMUNICATING HYDROCEPHALUS - O. B. Bogomyakova; Yu. A. Stankevich; N. A. Mesropyan; L. A. Shraybman; A. A. Tulupov (Вестник рентгенологии и радиологии, 2016)
Objective: to determine differences in cerebrospinal fluid (CSF) flow velocities in patients with varying degrees of communicating hydrocephalus (CH) versus a group of healthy volunteers without hydrodynamic disorders. Material and methods. The investigation enrolled 27 CH patients (17 and 10 patients with an Evans index of 0.31 and 0.46, respectively) and 62 healthy volunteers. Average, volumetric, and peak flow velocities were determined at different intracranial levels. Results. Analysis of differences between the mean values indicated that the patients with CH were observed to have progressive cranial cavity CSF outflow obstruction that depended on the degree of dilation of the ventricular system and, probably, on impaired CSF reabsorption. These changes can provide an explanation for the clinical symptoms present in the patients and also serve as diagnostic criteria. Conclusion. The investigation showed that phase-contrast magnetic resonance imaging might be used to estimate the quantitative indicators of CSF in health and in varying degrees of CH. The velocity characteristics of antegrade and retrograde CSF flows are significantly different in health and in disease, which may be relevant to neurologists and neurosurgeons when planning therapy and surgery options.